Nation Branding: Unveiling Factors that Affect the Image of Colombia from a Foreign Perspective (2019)
Most countries are concerned about the image they project in international markets. They have adopted and implemented differentiation strategies in order to stimulate tourism and economic investment. In the case of Colombia's reputation, it has been built on unplanned positioning, interests and views of a few opinion leaders, political and economic instability and transformations in the productive sector. This paper outlines, using a Bayesian variable selection approach, the perception of foreign visitors and prospects on Colombia's country image, and proposes a methodological framework for unvailing those driving factors. Findings of this research demonstrate that countries may be seen positively from the point of view of visitors while prospects may have a negative image of them. The results validate the hypothesis that the symbolic elements associated with a country's image, in this case with Colombia's image, should be included in the communication activities of a country branding strategy. © 2017, © 2017 Informa UK Limited, trading as Taylor and Francis Group.